An introduction to Autoclaved Aerated Concrete including design requirements using strength design - Domingo, Eric Ray (Kansas State University, 2008)
Autoclaved Aerated Concrete (AAC) is a lightweight concrete building material cut into masonry blocks or formed larger planks and panels. Currently it has not seen widespread use in the United States. However, in other parts of the world it use has been used successfully as a building material for over fifty years. AAC is a relatively new (at least to the United States) concrete masonry material that is lightweight, easy to construct, and economical to transport. Its light weight is accomplished through the use of evenly distributed microscopic air bubbles throughout the material; these bubbles result in a lightweight concrete that is composed of a latticework around spherical voids. This report details the history, physical properties, manufacturing process, and structural design of AAC. This report includes an explanation of the 2005 Masonry Standards Joint Committee (MSJC) Code for the design of AAC members subjected to axial compressive loads, bending, combined axial and bending, and shear. An example building design using AAC structural components is provided. This report concludes that AAC has important advantages as a structural building material that deserves further consideration for use in the United States.
Keywords: AAC; Autoclaved Aerated Concrete; Architecture (0729); Engineering, Civil (0543)